Retinal Migraine: from History to the Present Day - N. L. Sheremet (Oftalʹmologiâ)
Retinal migraine is a rare migraine variant, initially described in 1882 as ‘ophthalmic megrim’. Since then, various terms have been used in the literature, such as “ocular migraine”, “monocular migraine”, and “migraine of the anterior visual pathway”. The lack of an unified definition led to controversy and potential confusion in defining the diagnosis. Later, the International Classification of Headache Disorders (ICHD-3) defined retinal migraine as repeated attacks of monocular visual disturbance, including scintillation, scotoma or blindness, associated with migraine headache, which are fully reversible. Retinal migraine should be considered a diagnosis of exclusion that requires ruling out other causes of transient monocular vision loss. The purpose of this review is to analyze the data on the prevalence, pathogenesis, clinical presentation, and differential diagnosis of retinal migraine reported in the literature.